BER AND PAPR ANALYSIS OF 8X8 MIMO OFDM SYSTEM USING SLM TECHNIQUE - Sharma, Anurag (My University, 2013)
Increased spectral efficiency and improved link reliability are major challenges in future wireless communications system design. The radio channel constitutes a hostile propagation medium, which suffers from fading and interference from other users. With the evolution of the wireless system the demand for high speed data services have been increasing day by day, which is impossible to be achieve by the conventional serial data transmission system without trade-off between high speed data services and QOS without increasing the band width of the system. So both the options are inconvenient, as one never demands the degradation of the service quality and secondly the need for extra spectrum in a limited spectrum scenario. In order to overcome this problem new parallel data transmission system was proposed, which is known as OFDM system. The performance of OFDM system can further be improved by using multiple antennas at transmitting and receiving side to provide spatial diversity. Multiple antennas can be used at the transmitter and receiver, an arrangement called a MIMO system. A MIMO system takes advantage of the spatial diversity that is obtained by spatially separated antennas in a dense multipath scattering environment. Recently, there have been a lot of interests in combining the OFDM systems with the multiple-input multiple-output (MIMO) technique. These systems are known as MIMO-OFDM systems. MIMO-OFDM system has been currently recognized as one of the most competitive technology for 4G mobile wireless systems. The combination of OFDM and MIMO seems to be very promising when aiming at the design of very high-rate wireless mobile systems. While multiple antennas at the transmitter and receiver elevate channel capacity, i.e. the achievable transmission rate, OFDM converts the wideband frequency selective radio channel into a set of parallel flat-fading channels, thus simplifying signal processing required at the receiver. The main drawback of MIMO-OFDM system is high peak-to-average power ratio (PAPR) for large number of sub-carriers, which result in many restrictions for practical applications. Coding, phase rotation and clipping are among many PAPR reduction schemes that have been proposed to overcome this problem. In this thesis, BER and PAPR of 8x8 MIMO OFDM system is calculated and the PAPR is reduced using SLM(Selected Mapping) Technique.
ME, ECED
Keywords: BER; PAPR; MIMO-OFDM; QPSK